Superhydrophobic porous networks for enhanced droplet shedding - Liu, Yahua (Sci Rep, 2016)
Recent research has shown that the use of submillimeter-scale tapered post arrays could generate the so-called pancake bouncing, which is characterized by the fast shedding of impinging drops from the surface in a pancake shape without undergoing the retraction stage as observed on conventional superhydrophobic surfaces. Despite this exciting discovery, the fabrication of this unique superhydrophobic surface with tapered post arrays involves complex processes, hindering its wide applications in practical sectors. Here, we report on the facile strategy to prepare a new hierarchical multilayered superhydrophobic surface directly from commercially available porous matrix that allows for efficient drop shedding. Further study shows that the enhanced drop mobility observed on such a surface is attributed to the synergistic cooperation of hierarchical structures endowing an adequate energy storage and effective energy release. The facile fabrication of superhydrophobic surface with enhanced drop mobility may find many practical applications including anti-icing, dropwise condensation and self-cleaning.